METODE FTIR PADA KARAKTERISASI MISELIUM JAMUR TIRAM PUTIH DENGAN BIBIT BERMEDIA SORGUM - Ana Fitriana; Fitrah Hadi Firdaus; Irlian Nurmaniah; Maya Risanti; Mersi Kurniati; Irzaman Irzaman (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
Oyster mushroomâ€™s mycelium was inoculated by sorgum mediaâ€™s seed were done. FTIR analisys in 400-4000 cm-1 of wave length showed that oyster mushroomâ€™s mycelium possessed of O-H, C-H,         C-O, and C=O molecul. O-H molecul showed Î²-glucan and C-H, C-O, and C=O molecul showed aldehyd, ester, and keton cluster.Keywords: cluster, FTIR, mycelium, oyster mushroom, sorgum.